Optimization of an azetidine series as inhibitors of colony stimulating factor-1 receptor (CSF-1R) Type II to lead to the clinical candidate JTE-952. Issue 7 (1st April 2019) - Ikegashira, Kazutaka; Ikenogami, Taku; Yamasaki, Takayuki; Oka, Takahiro; Hase, Yasunori; Miyagawa, Naoki; Inagaki, Koji; Kawahara, Iichiro; Koga, Yoshihisa; Hashimoto, Hiromasa
Graphical abstract: Highlights: JTE-952 (( S )-8b ) as a CSF-1R Type II inhibitor show high kinase selectivity. JTE-952 (( S )-8b ) showed high cellular potency (IC50  = 20 nM) and in vivo effect. JTE-952 (( S )-8b ) was effective against a mouse collagen-induced model of arthritius (mouse CIA-model). JTE-952 (( S )-8b ) was identified as a clinical candidate for RA. Abstract: Optimization of novel azetidine compounds, which we had found as colony stimulating factor-1 receptor (CSF-1R) Type II inhibitors, providedJTE-952 as a clinical candidate with high cellular activity (IC50  = 20 nM) and good pharmacokinetics profile.JTE-952 was also effective against a mouse collagen-induced model of arthritis (mouse CIA-model). Additionally, the X-ray co-crystal structure ofJTE-952 with CSF-1R protein was shown to be a Type II inhibitor, and the kinase panel assay indicated thatJTE-952 had high kinase selectivity.